Peningkatan Kompetensi Dalam Menunjang Kinerja Karyawan Pada PT Batang Bumi Mandiri - Dekky SI Efendi; Sonny Hersonna; DJ Suyaman (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
Competence in an organization or company is important in supporting the performance produced by employees. The management of course will make efforts to increase the competence of its employees with the hope that the performance of the employees will make their work complete and the output produced is of high quality. Recognizing the importance of competence on performance, the authors helped by examining these variables. In this study the researchers collected data by distributing it to all employees at PT Batang Bumi Mandiri with a total of 25, of which the entire population will also be sampled because the sampling method used is the saturated sample technique. In processing this data used statistical data processing tools in the form of SPSS version 26 to assist the author in processing research data. The result of the research is that competence has an effect on performance. The competency variable also has a coefficient of determination of 16.5% to affect performance, while the remaining 83.5% is influenced by other variables not examined in this study.